THE SURFACE CHARACTERISTICS AND PHYSICAL PROPERTIES OF SENGON WOOD AT HIGH-TEMPERATURE HEATING TREATMENTS - Fariha, Tushliha Ayyuni; Marbun, Sari D; Sudarmanto; Narto; Bahanawan, Adik; Sejati, Prabu S; Darmawan, Teguh; Triwibowo, Dimas; Adi, Danang S; Amin, Yusup; Augustina, Sarah; Dwianto, Wahyu; Sari, Rita K; Alipraja, Irsan; Wahyudi, Imam; Kusuma, EM. Latif R (Indonesian Journal of Forestry Research, 2025)
Sengon (Falcataria moluccana Miq.) is a fast-growing timber species widely distributed in Indonesia. However, its dimensional instability and low surface quality have limited its widespread use. Wood modification is essential for enhancing these properties, and one effective approach is heat treatment. This study investigated the effects of different heat treatment methods and durations on color change, surface roughness, weight loss (WL), decreased density, and dimensional stability of sengon wood. The heat modification process was conducted using two methods: oven-heating and hot press-heating, with temperatures set at 200°C for durations ranging from 1 to 5 hours. The results indicated that oven-heated samples exhibited higher surface roughness, weight loss, density reduction, and dimensional stability while showing less color change than hot press-heated samples. Additionally, the hot press-heated samples displayed more significant color changes (darkening) and smoother surface roughness. WL and decreased density were also more pronounced with longer heating durations, except for the 4- and 5-hour hot press-heating treatments. Notably, oven-heated samples demonstrated higher dimensional stability than hot press-heated samples as the duration of heating increased. Based on the results, the optimal treatment varies depending on the desired product characteristics. For improved surface qualities with consideration of WL, the optimum treatment is a 2-hour hot press-heating treatment. Higher dimensional stability can be achieved through a 3-hour oven-heating treatment.